2000
DOI: 10.1002/1097-010x(20000815)288:2<151::aid-jez6>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and tail length divergence in mice selected for rate of development

Abstract: A series of mouse lines has been produced by 19 generations of restricted index selection for rate of development during early and late ontogeny. The selection program was based on an index with the following four replicated selection treatments: E+ and E– were selected to alter birth to 10‐day body weight gain while holding late gain for both selection lines constant; correspondingly, L+ and L– were selected to alter 28‐ to 56‐day body weight gain holding early gain for both lines constant. Herein, we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The higher endocortical osteoblastic parameters in 4-wk-old KO mice might indicate greater bone length rather than cross-sectional changes. This finding was confirmed with the measurements of tibia and tail length, which are easily obtained parameters for mouse growth rate (35). Both 4-and 10-wk-old KO mice showed significantly longer tails, while the length of the tibia was longer in KO mice by 10 wk of age.…”
Section: Discussionsupporting
confidence: 78%
“…The higher endocortical osteoblastic parameters in 4-wk-old KO mice might indicate greater bone length rather than cross-sectional changes. This finding was confirmed with the measurements of tibia and tail length, which are easily obtained parameters for mouse growth rate (35). Both 4-and 10-wk-old KO mice showed significantly longer tails, while the length of the tibia was longer in KO mice by 10 wk of age.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, for the two ontogenies that changed in shape and position as a result of selection (wheel running and food consumption), drift only influenced the control line; however, for the ontogeny that changed only in position as a result of selection (body mass), drift affected both the selected and control lines. Other studies have observed similar effects of genetic drift on the genetic architecture of trait ontogenies (Rhees and Atchley 2000) and of correlated traits (Arnold and Phillips 1999;Roff and Mousseau 1999;Roff 2000;Phillips et al 2001), demonstrating that genetic drift can significantly influence the rate and direction of evolutionary change and that its effects in nonselected populations, at least for some traits may be stronger (but see Garland et al 2002).…”
Section: Genetic Driftmentioning
confidence: 77%
“…Interestingly, the conducted DEXA total body scan showed that despite exhibiting the same daily energy intake, mice in the DEH group showed reduced physical growth compared to those in the CON group (Table 1). Specifically, the DEH mice exhibited a 5% (p < 0.05) reduction in lean body mass and a 9% (p < 0.05) reduction of their tail length, which is considered to be a standard growth indicator of rodent growth [23]. Therefore, these data suggest that dehydration incurs deleterious impacts on physical growth during the examined developmental period in young mice.…”
Section: Long-term Dehydration Induces Growth Retardation In Young Micementioning
confidence: 80%